Հուշանգ Մորադի Քերմանիի ստեղծագործությունները - Մահմուդ Ֆիրուզիմողադամ (ՀՀ ԳԱԱ հրատ.)
Статья посвящена анализу книги "Повести Маджиди", написанной иранским писателем и сатириком Ушанг Моради, которая состоит из 39 историй. Автор приходит к выводу, что сюжеты и образы многих произведений Марка Твена и Моради Кермани взяты из личной жизни этих писателей, и что очевидная общность написанных ими повестей как раз и состоит в том, что оба они рассказывают свои собственные истории.The article is devoted to the analysis of “Majidi stories” written by Iranian writer and humorist Hushang Moraddi, which consists of 39 stories. The author concludes that the works of Mark Twain and Moraddi Qermani are taken from the life stories of the mentioned renowned writers and the obvious common features of these writers factually consist in the fact that they both have recorded their own stories.
Keywords: Language and Literature